Addressing cell-sourcing limitations with gene therapy. - Garcia, A.J (IEEE Engineering in medicine and biology magazine)
Genetic engineering with Run×2/Cbfa 1 for an alternative to biological grafts. Forced Runx2 expression via retroviral gene delivery promotes osteoblastic differentiation and mineralization in bone marrow stromal cells and stimulates conversion of myoblasts and dermal fibroblasts into a mineralizing osteoblastic phenotype. This genetic engineering strategy provides a promising approach to overcome cell-sourcing limitations in bone tissue engineering.